Investigation of the Association Between Bone Mineral Density and Predisposing Factors in Osteoporotic Postmenopausal Women in a Sample of Patients From Gaziantep and Trabzon - Ercan Madenci; Murat Karkucak; Mustafa Güler; Savaş Gürsoy; Sema Keven (Galenos Yayinevi, 2003)
Our objective was to investigate the association between the bone mineral density and risk factors predisposing to osteoporosis as well as impact of regional factors on bone mineral density by comparing the data obtained from patients who lived in Gaziantep (a province in the south east of this country) and Trabzon (a province in the north east of this country). Included in the study were 318 patients, of whom 162 were from Gaziantep and 156 from Trabzon. Bone mineral density of the patients was measured with DEXA, and those who had a t score below (-2.0) SD on bone mineral density measurement in the back and hip regions were included in the study. An osteoporosis follow up questionnaire that was modified from MEDOS study questionnaire was filled. The patients who lived in Gaziantep were fatter than those who lived in Trabzon (p<0.001). The height and age of the patients were also different significantly (p>0.05). The bone mineral density (L2-4 femur (total) and Wards triangle) of the patients who lived in Trabzon was significantly lower than in Gaziantep (p<0.001). There was no statitical difference between the two groups regarding hair color, coffee and dressing habits, daily milk consumption, history of maternal milk ingestion, and alcohol and cigarette abuse (p>0.05). White skin color and high tea consumption were more common in the second group (p<0.001). Some parameters like dark or wheat skin and black eye color, birth and abortion rate, and sun bathing habis were more common in the first group (p<0.001). In conclusion, fist and cost effective option to estimate whether the patient carries a high risk is to evaluate the place where the patient lives as well the habits and traditions. The proceeding bone mineral density measurement will help to diagnose the disease. We believe that this approach will help not only for early diagnosis of osteoporosis but also useful economically.